Impact of inadequate initial antimicrobial therapy on mortality in patients with bacteraemic cholangitis: a retrospective cohort study. (October 2017) - Tagashira, Y.; Sakamoto, N.; Isogai, T.; Hikone, M.; Kosaka, A.; Chino, R.; Higuchi, M.; Uehara, Y.; Honda, H.
Abstract: Objectives: Acute cholangitis is a common cause of bacteraemia resulting in severe sepsis or septic shock. The impact of the appropriate initial antimicrobial therapy on short-term mortality in bacteraemic cholangitis has not been well investigated. Methods: We conducted a retrospective cohort study of patients with bacteraemic cholangitis at two large tertiary care centres in Tokyo, Japan between 2009 and 2015. We determined the factors associated with 30-day all-cause mortality from the date of drawing the first positive blood culture, using a multivariate logistic regression analysis. Results: We identified 573 patients with bacteraemic cholangitis (median age, 77 years; male, 58.3%). The 30-day all-cause mortality rate was 6.6% (38/573). Inadequate initial antimicrobial therapy occurred in 133 (23.2%) patients. Factors associated with 30-day all-cause mortality included the Charlson co-morbidity index score >3 (adjusted odds ratio (aOR) 4.12; 95% CI 1.18–14.38), jaundice (total bilirubin >2.5 mg/dL) (aOR 3.39; 95% CI 1.46–7.89), septic shock within 48 h of the first positive blood culture (aOR 3.34; 95% CI 1.42–7.89), biliary obstruction due to hepatobiliary malignancy (aOR 8.00; 95% CI 2.92–21.97), and inadequate initial antimicrobial therapy (aOR 2.78; 95% CI 1.27–6.11). Conclusions: Inadequate initial antimicrobial therapy was an important, modifiable determinant of survival.